PENGGUNAAN PENGETAHUAN MASYARAKAT DALAM PEMANFAATAN TANAMAN UNTUK PANGAN DAN OBAT DI AGROFORESTRY GUNUNG DAMAR GORONTALO - Dunggio, Iswan (Universitas Lambung Mangkurat, 2024)
The practice of agroforestry in the Gunung Damar area, managed by the local community, is based on knowledge passed down through generations. The survival of agroforestry systems in the tropics, including the Gunung Damar agroforestry system, is due to the experience inherited from generation to generation. This accumulated experience shapes the knowledge of the people around Mount Damar in determining how to utilize agroforestry. This study aims to identify how community knowledge is applied in the use of plants for food and medicinal purposes in the Gunung Damar agroforestry garden. The data was collected through surveys and focus group discussions (FGDs), while data analysis was conducted using the Importance Value Index (LUVI). The results showed that 16 plant species were identified for medicinal use, and 10 plant species as food sources in the Gunung Damar agroforestry system. Four medicinal plants with the highest LUVI indices were Myristica fragrans (0.57), Zingiber officinale (0.46), Curcuma longa (0.46), and Cinnamomum verum (0.41). Meanwhile, the food sources with the highest indices were Arenga pinnata (3.16), Syzygium aromaticum (2.26), and Aleurites moluccana (0.90)